2017
DOI: 10.1002/ajmg.a.38275
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi sarcoma, oral malformations, mitral dysplasia, and scoliosis associated with 7q34‐q36.3 heterozygous terminal deletion

Abstract: Chromosome 7 germline macrodeletions have been implicated in human congenital malformations and developmental delays. We herein report a novel heterozygous macrodeletion of 7q34-q36.3 in a 16-year-old girl originally from West Indies. Similar to previously reported cases of germline chromosome 7q terminal deletions, our patient has dental malposition, and developmental (growth and intellectual) delay. Novel phenotypic features include endemic Kaposi sarcoma, furrowed tongue, thoracolumbar scoliosis, and mild m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Finally, CUL1 can regulate the β-catenin and Wnt pathways, which play a crucial role in body development (Wei et al, 2007). In fact, another four genes (SHH, LMBR1, KCNH2, and PRKAG2) may also affect the phenotypes of 7q terminal deletion syndrome (Hyohyeon and Lee, 2015;Jackson et al, 2017). First, SHH and LMBR1 are responsible for bone and tooth development; therefore, most 7q terminal deletion patients may show microcephaly, abnormal hand, and scoliosis (Rush et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, CUL1 can regulate the β-catenin and Wnt pathways, which play a crucial role in body development (Wei et al, 2007). In fact, another four genes (SHH, LMBR1, KCNH2, and PRKAG2) may also affect the phenotypes of 7q terminal deletion syndrome (Hyohyeon and Lee, 2015;Jackson et al, 2017). First, SHH and LMBR1 are responsible for bone and tooth development; therefore, most 7q terminal deletion patients may show microcephaly, abnormal hand, and scoliosis (Rush et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known regarding 7q terminal deletions in contiguous gene deletion syndrome. The typical clinical features of 7q terminal deletion syndrome include abnormal brain and facial structures, developmental delay, intellectual disability, abnormal limbs, and sacral anomalies ( Rush et al, 2013 ; Jackson et al, 2017 ). At present, 7q terminal deletion syndrome has only been described in 28 patients, most of whom had 7q36 microdeletions ( Jackson et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 , 23 ] We compare the similar deletion regions and clinical features in patients with 7q34-q36.3 overlapped in Table 2 , [ 6 , 8 , 23 29 ] which present common characteristics as shown. Roessler et al [ 28 ] and Jackson et al [ 26 ] separately reported deletions of 7q34-qter and 7q34-q36.3; the sharing clinical phenotype is microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…Our case happened to be a female with a duplication of 4q34.1q35.2 and abnormal kidney ultrasound findings, which aroused our interest that 4q34 may be an interesting region in renal hypoplasia. In addition, Jackson et al [ 26 ] speculated that renal malformations may mainly be associated with 7q36.1-qter deletion and 7q35 deletion, and there maybe exist genitourinary development putative genes at these regions. Also, the research of Caselli et al [ 25 ] suggested that the deletion of 7q36.1 and 7q36.2 have more links with renal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…KS is very rare in children, and this is particularly true for classic KS, less than 50 cases of which have been reported in children [88]. Six different genetic etiologies of KS have been reported, all in children with classic KS [88]: IFNγRl deficiency [89], Wiskott-Aldrich syndrome (WAS) [90], STIM1 deficiency [91], OX40 deficiency [92], MAGT1 deficiency [93], and a large deletion on chromosome 7 [94], each in a single patient. It is difficult to draw any firm conclusions for such a small sample of patients displaying such a high degree of genetic heterogeneity.…”
Section: Hhv8 Infection and Kaposi Sarcoma (Ks) In Patients With Pids Or Hivmentioning
confidence: 99%